Do Broadband Usage and Telecommunications Competition Support Employment and Poverty Reduction Efforts? Arab and EU Comparison - Mohammad Ahmad Almomani; Bashir Khalifeh Al Zu ‘bi (دراسات العدد الاقتصادي, 2025)
This study aims to measure the impact of using fixed and mobile broadband telecommunications services on employment and poverty reduction, the study uses the actual volume of data used to measure the broadband usage and the ICT regulatory tracker index as a proxy to measure the competition level in telecommunications sector. The study used two econometric models, the first one to measure the impact on employment and the second to measure the impact on poverty reduction, and were applied to two groups of samples: Group 1 represents EU countries, and Group 2 represents Arab countries; a generalized least squares method is used to estimate the model’s parameters. The results show that using broadband services has positive and significant impacts on employment and poverty reduction in both groups, but the effect in EU countries was higher than in Arab. Competition level in the telecommunications sector has a contradicted and inconclusive impact on both groups. Based on the results, the study recommends adopting policies that may enhance fixed and broadband usage. Such as actions to be taken with regard to universal service policies and national broadband plans.